Comparison of Safety Perception between Foreign and Local Workers in the Construction Industry in Republic of Korea - Serdar Korkmaz; Dal Jae Park (Elsevier, 2018)
Background: Since the Republic of Korea became a labor-force-importing country, the number of foreign workers has increased gradually, especially in the construction industry. The main objective of this study was to examine the differences in safety perception between domestic and foreign workers at Korean construction sites. Methods: A total of 891 Korean and foreign workers were surveyed: 140 foreign and 751 Korean workers. The general characteristics and 25 factors influencing safety perception were considered in the questionnaire. Regression and correlation analyses were conducted to examine the variables of workers' safety perception. Results: Differences of nationality (F = 7.379, p < 0.001) and workplace accidents were statistically significant for both domestic (F = 1.503, p < 0.05) and foreign workers (F = 7.868, p < 0.05). In contrast, age, education, and Korean language level were significant variables only for foreign workers. Correlation coefficients of 0.428** for Korean and 0.148 for foreign workers between two items - namely, "management's commitment to safety" and "blaming staff when they make mistakes" - support the conclusion that foreign workers do not trust management's commitment to safety, while Korean workers have confidence in these commitments. Conclusion: Foreign workers' level of safety perception should rise to the same level as Korean workers, especially in terms of obeying safety rules, safety education performance, and safety beliefs. Therefore, an improvement plan for the Korean construction industry is suggested in order to have a better safety level at construction sites with foreign workers. Keywords: construction, foreign workers, Korean workers, safety perception